2021
DOI: 10.3390/molecules26216663
|View full text |Cite
|
Sign up to set email alerts
|

Role of Surface Preparation in Corrosion Resistance Due to Silane Coatings on a Magnesium Alloy

Abstract: Coating of an organo-silane (Bis-1,2-(TriethoxySilyl)Ethane (BTSE)) has been observed to improve the corrosion resistance of magnesium alloy AZ91D. Three different types of surface preparations have been employed before condensing the silane coating on to the substrate. Corrosion resistance was investigated using electrochemical impedance spectroscopy (EIS). A specific alkali treatment of the substrate prior to the coating has been found to improve the corrosion resistance of the coated alloy, which has been a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In addition to adding fillers during the preparation of sol-gel, some scholars have found that the substrate treatment (i.e., acid treatment, alkali treatment, heat treatment) will also affect the protective effect of sol-gel coatings. Saxena et al found that specific alkali treatments of the Mg substrate before sol-gel coating can improve the corrosion resistance of the coatings because they can promote the sol-gel condensation process [ 90 ]. Supplit et al studied the anticorrosion effect of the sol-gel coating on the AZ31 Mg alloy after the substrate was pickled with hydrofluoric acid, phosphoric acid, nitric acid, and acetic acid [ 91 ].…”
Section: Bare Sol-gel Coatingsmentioning
confidence: 99%
“…In addition to adding fillers during the preparation of sol-gel, some scholars have found that the substrate treatment (i.e., acid treatment, alkali treatment, heat treatment) will also affect the protective effect of sol-gel coatings. Saxena et al found that specific alkali treatments of the Mg substrate before sol-gel coating can improve the corrosion resistance of the coatings because they can promote the sol-gel condensation process [ 90 ]. Supplit et al studied the anticorrosion effect of the sol-gel coating on the AZ31 Mg alloy after the substrate was pickled with hydrofluoric acid, phosphoric acid, nitric acid, and acetic acid [ 91 ].…”
Section: Bare Sol-gel Coatingsmentioning
confidence: 99%
“…Like acid treatment, alkali treatment is also a simple chemical conversion coating method to produce a Mg(OH) 2 layer on the surface by treating it with a suitable alkaline medium (Saxena and Raman, 2021). Gu et al (2009) compared the effect of different alkaline mediums, namely, disodium phosphate, sodium bicarbonate, and sodium carbonate, on Mg-Ca alloy.…”
Section: Alkali Treatmentmentioning
confidence: 99%